HANDLING OF MEMBERS WHO FAIL TO PAY DUE TO DEATH FROM AN ISLAMIC PERSPECTIVE: Case Study at KSPPS Guna Lestari Jaya Tegalsambi Branch - Amalia, Lutfi Nur; Mubarok, Ahmad Fauzan; Ansori, Miswan (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
Sharia Financing Savings and Loans Cooperative (KSPPS) as a sharia microfinance institution has an important role in empowering the community's economy based on Islamic principles. One of the challenges faced is the risk of default due to the death of a member, which can have an impact on the sustainability of the institution and raise issues of justice. This study aims to determine the mechanism for handling cases of default due to death at KSPPS Guna Lestari Jaya Tegalsambi Branch, to analyze its compliance with sharia principles from an Islamic economic perspective, and the implications for institutional sustainability and member welfare. The research method used is qualitative descriptive with data collection techniques through interviews, observations, and documentation. The results of the study indicate that KSPPS Guna Lestari Jaya implements settlement through deliberation, tabarru' funds, and a sharia insurance scheme (ta'awun) according to previous agreements. This mechanism reflects the principles of mutual assistance, social responsibility, and justice, and avoids elements of usury and gharar. Thus, the handling of default due to death at this KSPPS is in accordance with Islamic economic principles.